Tinjauan Yuridis Penerapan Asas Nebis In Idem Oleh Hakim dalam Perkara Perceraian di Pengadilan Negeri Mungkid - Syarifatul Fadhilah; Listyowati Dewi; Arum Nurul Layalia Mufaidah; Gita Jemima Ardhana; Rani Pajrin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Marriage is a spiritual and physical bond between one man and one woman as husband and wife with the aim of forming a happy family based on the belief in the Almighty God. In a marriage, forming a happy family certainly requires cooperation between each party, both husband and wife. If both parties have different goals, it will trigger problems in the household. Problems in the household can influence divorce between both parties, namely husband and wife. Divorce is a condition in the household where there is no common ground for harmony and harmony in the relationship between husband and wife so that it can be decided by the District Court for those of non-Islamic religions or the Religious Court for those of Islamic religion. Considering that Indonesia is a country of law where every action has rules, if seen from the principle of Nebis In Idem, this problem is no longer acceptable. However, in this divorce case the lawsuit was accepted by the judge and the judge decided again with a different decision. Based on this, the formulation of the problem is how to apply the Ne Bis In Idem Principle by the judge in divorce cases